(587) Application of Some Models For Planning تطبيق بعض النماذج في التخطيط - M. El-Imam, M. (INP, 2023)
Since the beginning of the year 1965, research group as been formed in the Operation Research Center of the INPC, with the aim of studying the problem of Model- building for planning purposes, the final objective is to build up a series of models, each dealing with a specific number of development planning questions.